Are there coordination instabilities in the walk-to-run transition? A case study using self-organising maps - Bartlett, R.; O`Donovan, D.; Kennedy, G.; Saini, R. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study investigated multi-dimensional coordination instabilities in the transition between walking and running for a 26 year old female runner using self-organising maps (SOMs). We found different multi-dimensional coordination patterns for walking and running using the output from SOMs as stride trajectories on U-matrices and attractor diagrams. In the second experimental procedure, the participant showed clear transient multi-stability, or instability, at 8.2 km/h in the transition region for decreasing but not for increasing speeds; this is unlikely to be general across runners. She also showed increased multi-dimensional coordination variability around the transition region. SOMs provide us with a tool to study multi-dimensional coordination and to reduce its complexity to relatively simple map outputs.